MAYBE Initial complexity problem: 1: T: (1, 1) f0(a, b, c, d, e, f, g) -> f12(h, i, j, 0, e, f, g) (?, 1) f12(a, b, c, d, e, f, g) -> f12(a, b, c, d + 1, e, f, g) [ c >= d + 1 ] (?, 1) f25(a, b, c, d, e, f, g) -> f25(a, b, c, d, e, f + 1, g) [ e >= f + 1 ] (?, 1) f25(a, b, c, d, e, f, g) -> f34(a, b, c, d, e, f, g) [ f >= e ] (?, 1) f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 0, h) [ d >= c ] start location: f0 leaf cost: 0 Repeatedly removing leaves of the complexity graph in problem 1 produces the following problem: 2: T: (1, 1) f0(a, b, c, d, e, f, g) -> f12(h, i, j, 0, e, f, g) (?, 1) f12(a, b, c, d, e, f, g) -> f12(a, b, c, d + 1, e, f, g) [ c >= d + 1 ] (?, 1) f25(a, b, c, d, e, f, g) -> f25(a, b, c, d, e, f + 1, g) [ e >= f + 1 ] (?, 1) f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 0, h) [ d >= c ] start location: f0 leaf cost: 1 A polynomial rank function with Pol(f0) = 1 Pol(f12) = 1 Pol(f25) = -1 orients all transitions weakly and the transition f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 0, h) [ d >= c ] strictly and produces the following problem: 3: T: (1, 1) f0(a, b, c, d, e, f, g) -> f12(h, i, j, 0, e, f, g) (?, 1) f12(a, b, c, d, e, f, g) -> f12(a, b, c, d + 1, e, f, g) [ c >= d + 1 ] (?, 1) f25(a, b, c, d, e, f, g) -> f25(a, b, c, d, e, f + 1, g) [ e >= f + 1 ] (1, 1) f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 0, h) [ d >= c ] start location: f0 leaf cost: 1 Applied AI with 'oct' on problem 3 to obtain the following invariants: For symbol f12: X_4 >= 0 For symbol f25: X_6 >= 0 /\ X_4 + X_6 >= 0 /\ X_1 - X_5 >= 0 /\ -X_1 + X_5 >= 0 /\ X_4 >= 0 /\ -X_3 + X_4 >= 0 This yielded the following problem: 4: T: (1, 1) f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 0, h) [ d >= 0 /\ d >= c ] (?, 1) f25(a, b, c, d, e, f, g) -> f25(a, b, c, d, e, f + 1, g) [ f >= 0 /\ d + f >= 0 /\ a - e >= 0 /\ -a + e >= 0 /\ d >= 0 /\ -c + d >= 0 /\ e >= f + 1 ] (?, 1) f12(a, b, c, d, e, f, g) -> f12(a, b, c, d + 1, e, f, g) [ d >= 0 /\ c >= d + 1 ] (1, 1) f0(a, b, c, d, e, f, g) -> f12(h, i, j, 0, e, f, g) start location: f0 leaf cost: 1 By chaining the transition f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 0, h) [ d >= 0 /\ d >= c ] with all transitions in problem 4, the following new transition is obtained: f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 1, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 ] We thus obtain the following problem: 5: T: (1, 2) f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 1, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 ] (?, 1) f25(a, b, c, d, e, f, g) -> f25(a, b, c, d, e, f + 1, g) [ f >= 0 /\ d + f >= 0 /\ a - e >= 0 /\ -a + e >= 0 /\ d >= 0 /\ -c + d >= 0 /\ e >= f + 1 ] (?, 1) f12(a, b, c, d, e, f, g) -> f12(a, b, c, d + 1, e, f, g) [ d >= 0 /\ c >= d + 1 ] (1, 1) f0(a, b, c, d, e, f, g) -> f12(h, i, j, 0, e, f, g) start location: f0 leaf cost: 1 By chaining the transition f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 1, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 ] with all transitions in problem 5, the following new transition is obtained: f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 2, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 ] We thus obtain the following problem: 6: T: (1, 3) f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 2, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 ] (?, 1) f25(a, b, c, d, e, f, g) -> f25(a, b, c, d, e, f + 1, g) [ f >= 0 /\ d + f >= 0 /\ a - e >= 0 /\ -a + e >= 0 /\ d >= 0 /\ -c + d >= 0 /\ e >= f + 1 ] (?, 1) f12(a, b, c, d, e, f, g) -> f12(a, b, c, d + 1, e, f, g) [ d >= 0 /\ c >= d + 1 ] (1, 1) f0(a, b, c, d, e, f, g) -> f12(h, i, j, 0, e, f, g) start location: f0 leaf cost: 1 By chaining the transition f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 2, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 ] with all transitions in problem 6, the following new transition is obtained: f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 3, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 ] We thus obtain the following problem: 7: T: (1, 4) f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 3, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 ] (?, 1) f25(a, b, c, d, e, f, g) -> f25(a, b, c, d, e, f + 1, g) [ f >= 0 /\ d + f >= 0 /\ a - e >= 0 /\ -a + e >= 0 /\ d >= 0 /\ -c + d >= 0 /\ e >= f + 1 ] (?, 1) f12(a, b, c, d, e, f, g) -> f12(a, b, c, d + 1, e, f, g) [ d >= 0 /\ c >= d + 1 ] (1, 1) f0(a, b, c, d, e, f, g) -> f12(h, i, j, 0, e, f, g) start location: f0 leaf cost: 1 By chaining the transition f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 3, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 ] with all transitions in problem 7, the following new transition is obtained: f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 4, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 ] We thus obtain the following problem: 8: T: (1, 5) f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 4, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 ] (?, 1) f25(a, b, c, d, e, f, g) -> f25(a, b, c, d, e, f + 1, g) [ f >= 0 /\ d + f >= 0 /\ a - e >= 0 /\ -a + e >= 0 /\ d >= 0 /\ -c + d >= 0 /\ e >= f + 1 ] (?, 1) f12(a, b, c, d, e, f, g) -> f12(a, b, c, d + 1, e, f, g) [ d >= 0 /\ c >= d + 1 ] (1, 1) f0(a, b, c, d, e, f, g) -> f12(h, i, j, 0, e, f, g) start location: f0 leaf cost: 1 By chaining the transition f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 4, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 ] with all transitions in problem 8, the following new transition is obtained: f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 5, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 ] We thus obtain the following problem: 9: T: (1, 6) f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 5, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 ] (?, 1) f25(a, b, c, d, e, f, g) -> f25(a, b, c, d, e, f + 1, g) [ f >= 0 /\ d + f >= 0 /\ a - e >= 0 /\ -a + e >= 0 /\ d >= 0 /\ -c + d >= 0 /\ e >= f + 1 ] (?, 1) f12(a, b, c, d, e, f, g) -> f12(a, b, c, d + 1, e, f, g) [ d >= 0 /\ c >= d + 1 ] (1, 1) f0(a, b, c, d, e, f, g) -> f12(h, i, j, 0, e, f, g) start location: f0 leaf cost: 1 By chaining the transition f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 5, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 ] with all transitions in problem 9, the following new transition is obtained: f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 6, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 ] We thus obtain the following problem: 10: T: (1, 7) f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 6, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 ] (?, 1) f25(a, b, c, d, e, f, g) -> f25(a, b, c, d, e, f + 1, g) [ f >= 0 /\ d + f >= 0 /\ a - e >= 0 /\ -a + e >= 0 /\ d >= 0 /\ -c + d >= 0 /\ e >= f + 1 ] (?, 1) f12(a, b, c, d, e, f, g) -> f12(a, b, c, d + 1, e, f, g) [ d >= 0 /\ c >= d + 1 ] (1, 1) f0(a, b, c, d, e, f, g) -> f12(h, i, j, 0, e, f, g) start location: f0 leaf cost: 1 By chaining the transition f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 6, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 ] with all transitions in problem 10, the following new transition is obtained: f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 7, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 ] We thus obtain the following problem: 11: T: (1, 8) f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 7, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 ] (?, 1) f25(a, b, c, d, e, f, g) -> f25(a, b, c, d, e, f + 1, g) [ f >= 0 /\ d + f >= 0 /\ a - e >= 0 /\ -a + e >= 0 /\ d >= 0 /\ -c + d >= 0 /\ e >= f + 1 ] (?, 1) f12(a, b, c, d, e, f, g) -> f12(a, b, c, d + 1, e, f, g) [ d >= 0 /\ c >= d + 1 ] (1, 1) f0(a, b, c, d, e, f, g) -> f12(h, i, j, 0, e, f, g) start location: f0 leaf cost: 1 By chaining the transition f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 7, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 ] with all transitions in problem 11, the following new transition is obtained: f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 8, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 ] We thus obtain the following problem: 12: T: (1, 9) f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 8, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 ] (?, 1) f25(a, b, c, d, e, f, g) -> f25(a, b, c, d, e, f + 1, g) [ f >= 0 /\ d + f >= 0 /\ a - e >= 0 /\ -a + e >= 0 /\ d >= 0 /\ -c + d >= 0 /\ e >= f + 1 ] (?, 1) f12(a, b, c, d, e, f, g) -> f12(a, b, c, d + 1, e, f, g) [ d >= 0 /\ c >= d + 1 ] (1, 1) f0(a, b, c, d, e, f, g) -> f12(h, i, j, 0, e, f, g) start location: f0 leaf cost: 1 By chaining the transition f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 8, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 ] with all transitions in problem 12, the following new transition is obtained: f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 9, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 /\ 8 >= 0 /\ d + 8 >= 0 /\ a >= 9 ] We thus obtain the following problem: 13: T: (1, 10) f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 9, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 /\ 8 >= 0 /\ d + 8 >= 0 /\ a >= 9 ] (?, 1) f25(a, b, c, d, e, f, g) -> f25(a, b, c, d, e, f + 1, g) [ f >= 0 /\ d + f >= 0 /\ a - e >= 0 /\ -a + e >= 0 /\ d >= 0 /\ -c + d >= 0 /\ e >= f + 1 ] (?, 1) f12(a, b, c, d, e, f, g) -> f12(a, b, c, d + 1, e, f, g) [ d >= 0 /\ c >= d + 1 ] (1, 1) f0(a, b, c, d, e, f, g) -> f12(h, i, j, 0, e, f, g) start location: f0 leaf cost: 1 By chaining the transition f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 9, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 /\ 8 >= 0 /\ d + 8 >= 0 /\ a >= 9 ] with all transitions in problem 13, the following new transition is obtained: f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 10, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 /\ 8 >= 0 /\ d + 8 >= 0 /\ a >= 9 /\ 9 >= 0 /\ d + 9 >= 0 /\ a >= 10 ] We thus obtain the following problem: 14: T: (1, 11) f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 10, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 /\ 8 >= 0 /\ d + 8 >= 0 /\ a >= 9 /\ 9 >= 0 /\ d + 9 >= 0 /\ a >= 10 ] (?, 1) f25(a, b, c, d, e, f, g) -> f25(a, b, c, d, e, f + 1, g) [ f >= 0 /\ d + f >= 0 /\ a - e >= 0 /\ -a + e >= 0 /\ d >= 0 /\ -c + d >= 0 /\ e >= f + 1 ] (?, 1) f12(a, b, c, d, e, f, g) -> f12(a, b, c, d + 1, e, f, g) [ d >= 0 /\ c >= d + 1 ] (1, 1) f0(a, b, c, d, e, f, g) -> f12(h, i, j, 0, e, f, g) start location: f0 leaf cost: 1 By chaining the transition f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 10, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 /\ 8 >= 0 /\ d + 8 >= 0 /\ a >= 9 /\ 9 >= 0 /\ d + 9 >= 0 /\ a >= 10 ] with all transitions in problem 14, the following new transition is obtained: f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 11, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 /\ 8 >= 0 /\ d + 8 >= 0 /\ a >= 9 /\ 9 >= 0 /\ d + 9 >= 0 /\ a >= 10 /\ 10 >= 0 /\ d + 10 >= 0 /\ a >= 11 ] We thus obtain the following problem: 15: T: (1, 12) f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 11, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 /\ 8 >= 0 /\ d + 8 >= 0 /\ a >= 9 /\ 9 >= 0 /\ d + 9 >= 0 /\ a >= 10 /\ 10 >= 0 /\ d + 10 >= 0 /\ a >= 11 ] (?, 1) f25(a, b, c, d, e, f, g) -> f25(a, b, c, d, e, f + 1, g) [ f >= 0 /\ d + f >= 0 /\ a - e >= 0 /\ -a + e >= 0 /\ d >= 0 /\ -c + d >= 0 /\ e >= f + 1 ] (?, 1) f12(a, b, c, d, e, f, g) -> f12(a, b, c, d + 1, e, f, g) [ d >= 0 /\ c >= d + 1 ] (1, 1) f0(a, b, c, d, e, f, g) -> f12(h, i, j, 0, e, f, g) start location: f0 leaf cost: 1 By chaining the transition f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 11, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 /\ 8 >= 0 /\ d + 8 >= 0 /\ a >= 9 /\ 9 >= 0 /\ d + 9 >= 0 /\ a >= 10 /\ 10 >= 0 /\ d + 10 >= 0 /\ a >= 11 ] with all transitions in problem 15, the following new transition is obtained: f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 12, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 /\ 8 >= 0 /\ d + 8 >= 0 /\ a >= 9 /\ 9 >= 0 /\ d + 9 >= 0 /\ a >= 10 /\ 10 >= 0 /\ d + 10 >= 0 /\ a >= 11 /\ 11 >= 0 /\ d + 11 >= 0 /\ a >= 12 ] We thus obtain the following problem: 16: T: (1, 13) f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 12, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 /\ 8 >= 0 /\ d + 8 >= 0 /\ a >= 9 /\ 9 >= 0 /\ d + 9 >= 0 /\ a >= 10 /\ 10 >= 0 /\ d + 10 >= 0 /\ a >= 11 /\ 11 >= 0 /\ d + 11 >= 0 /\ a >= 12 ] (?, 1) f25(a, b, c, d, e, f, g) -> f25(a, b, c, d, e, f + 1, g) [ f >= 0 /\ d + f >= 0 /\ a - e >= 0 /\ -a + e >= 0 /\ d >= 0 /\ -c + d >= 0 /\ e >= f + 1 ] (?, 1) f12(a, b, c, d, e, f, g) -> f12(a, b, c, d + 1, e, f, g) [ d >= 0 /\ c >= d + 1 ] (1, 1) f0(a, b, c, d, e, f, g) -> f12(h, i, j, 0, e, f, g) start location: f0 leaf cost: 1 By chaining the transition f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 12, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 /\ 8 >= 0 /\ d + 8 >= 0 /\ a >= 9 /\ 9 >= 0 /\ d + 9 >= 0 /\ a >= 10 /\ 10 >= 0 /\ d + 10 >= 0 /\ a >= 11 /\ 11 >= 0 /\ d + 11 >= 0 /\ a >= 12 ] with all transitions in problem 16, the following new transition is obtained: f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 13, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 /\ 8 >= 0 /\ d + 8 >= 0 /\ a >= 9 /\ 9 >= 0 /\ d + 9 >= 0 /\ a >= 10 /\ 10 >= 0 /\ d + 10 >= 0 /\ a >= 11 /\ 11 >= 0 /\ d + 11 >= 0 /\ a >= 12 /\ 12 >= 0 /\ d + 12 >= 0 /\ a >= 13 ] We thus obtain the following problem: 17: T: (1, 14) f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 13, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 /\ 8 >= 0 /\ d + 8 >= 0 /\ a >= 9 /\ 9 >= 0 /\ d + 9 >= 0 /\ a >= 10 /\ 10 >= 0 /\ d + 10 >= 0 /\ a >= 11 /\ 11 >= 0 /\ d + 11 >= 0 /\ a >= 12 /\ 12 >= 0 /\ d + 12 >= 0 /\ a >= 13 ] (?, 1) f25(a, b, c, d, e, f, g) -> f25(a, b, c, d, e, f + 1, g) [ f >= 0 /\ d + f >= 0 /\ a - e >= 0 /\ -a + e >= 0 /\ d >= 0 /\ -c + d >= 0 /\ e >= f + 1 ] (?, 1) f12(a, b, c, d, e, f, g) -> f12(a, b, c, d + 1, e, f, g) [ d >= 0 /\ c >= d + 1 ] (1, 1) f0(a, b, c, d, e, f, g) -> f12(h, i, j, 0, e, f, g) start location: f0 leaf cost: 1 By chaining the transition f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 13, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 /\ 8 >= 0 /\ d + 8 >= 0 /\ a >= 9 /\ 9 >= 0 /\ d + 9 >= 0 /\ a >= 10 /\ 10 >= 0 /\ d + 10 >= 0 /\ a >= 11 /\ 11 >= 0 /\ d + 11 >= 0 /\ a >= 12 /\ 12 >= 0 /\ d + 12 >= 0 /\ a >= 13 ] with all transitions in problem 17, the following new transition is obtained: f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 14, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 /\ 8 >= 0 /\ d + 8 >= 0 /\ a >= 9 /\ 9 >= 0 /\ d + 9 >= 0 /\ a >= 10 /\ 10 >= 0 /\ d + 10 >= 0 /\ a >= 11 /\ 11 >= 0 /\ d + 11 >= 0 /\ a >= 12 /\ 12 >= 0 /\ d + 12 >= 0 /\ a >= 13 /\ 13 >= 0 /\ d + 13 >= 0 /\ a >= 14 ] We thus obtain the following problem: 18: T: (1, 15) f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 14, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 /\ 8 >= 0 /\ d + 8 >= 0 /\ a >= 9 /\ 9 >= 0 /\ d + 9 >= 0 /\ a >= 10 /\ 10 >= 0 /\ d + 10 >= 0 /\ a >= 11 /\ 11 >= 0 /\ d + 11 >= 0 /\ a >= 12 /\ 12 >= 0 /\ d + 12 >= 0 /\ a >= 13 /\ 13 >= 0 /\ d + 13 >= 0 /\ a >= 14 ] (?, 1) f25(a, b, c, d, e, f, g) -> f25(a, b, c, d, e, f + 1, g) [ f >= 0 /\ d + f >= 0 /\ a - e >= 0 /\ -a + e >= 0 /\ d >= 0 /\ -c + d >= 0 /\ e >= f + 1 ] (?, 1) f12(a, b, c, d, e, f, g) -> f12(a, b, c, d + 1, e, f, g) [ d >= 0 /\ c >= d + 1 ] (1, 1) f0(a, b, c, d, e, f, g) -> f12(h, i, j, 0, e, f, g) start location: f0 leaf cost: 1 By chaining the transition f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 14, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 /\ 8 >= 0 /\ d + 8 >= 0 /\ a >= 9 /\ 9 >= 0 /\ d + 9 >= 0 /\ a >= 10 /\ 10 >= 0 /\ d + 10 >= 0 /\ a >= 11 /\ 11 >= 0 /\ d + 11 >= 0 /\ a >= 12 /\ 12 >= 0 /\ d + 12 >= 0 /\ a >= 13 /\ 13 >= 0 /\ d + 13 >= 0 /\ a >= 14 ] with all transitions in problem 18, the following new transition is obtained: f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 15, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 /\ 8 >= 0 /\ d + 8 >= 0 /\ a >= 9 /\ 9 >= 0 /\ d + 9 >= 0 /\ a >= 10 /\ 10 >= 0 /\ d + 10 >= 0 /\ a >= 11 /\ 11 >= 0 /\ d + 11 >= 0 /\ a >= 12 /\ 12 >= 0 /\ d + 12 >= 0 /\ a >= 13 /\ 13 >= 0 /\ d + 13 >= 0 /\ a >= 14 /\ 14 >= 0 /\ d + 14 >= 0 /\ a >= 15 ] We thus obtain the following problem: 19: T: (1, 16) f12(a, b, c, d, e, f, g) -> f25(a, b, c, d, a, 15, h) [ d >= 0 /\ d >= c /\ 0 >= 0 /\ -c + d >= 0 /\ a >= 1 /\ 1 >= 0 /\ d + 1 >= 0 /\ a >= 2 /\ 2 >= 0 /\ d + 2 >= 0 /\ a >= 3 /\ 3 >= 0 /\ d + 3 >= 0 /\ a >= 4 /\ 4 >= 0 /\ d + 4 >= 0 /\ a >= 5 /\ 5 >= 0 /\ d + 5 >= 0 /\ a >= 6 /\ 6 >= 0 /\ d + 6 >= 0 /\ a >= 7 /\ 7 >= 0 /\ d + 7 >= 0 /\ a >= 8 /\ 8 >= 0 /\ d + 8 >= 0 /\ a >= 9 /\ 9 >= 0 /\ d + 9 >= 0 /\ a >= 10 /\ 10 >= 0 /\ d + 10 >= 0 /\ a >= 11 /\ 11 >= 0 /\ d + 11 >= 0 /\ a >= 12 /\ 12 >= 0 /\ d + 12 >= 0 /\ a >= 13 /\ 13 >= 0 /\ d + 13 >= 0 /\ a >= 14 /\ 14 >= 0 /\ d + 14 >= 0 /\ a >= 15 ] (?, 1) f25(a, b, c, d, e, f, g) -> f25(a, b, c, d, e, f + 1, g) [ f >= 0 /\ d + f >= 0 /\ a - e >= 0 /\ -a + e >= 0 /\ d >= 0 /\ -c + d >= 0 /\ e >= f + 1 ] (?, 1) f12(a, b, c, d, e, f, g) -> f12(a, b, c, d + 1, e, f, g) [ d >= 0 /\ c >= d + 1 ] (1, 1) f0(a, b, c, d, e, f, g) -> f12(h, i, j, 0, e, f, g) start location: f0 leaf cost: 1 Complexity upper bound ? Time: 2.328 sec (SMT: 2.130 sec)